Pesantren sebagai alat untuk mengurangi praktik carok di Madura - Lutfiyah, Jamilatul (Maliki Interdisciplinary Journal, 2024)
To make today’s young people into a generation of the nation with good intellectual and moral qualities, education is needed to support these dreams. However, the provisions provided by education to young people are not enough to face the period of becoming adults and living together interacting with the wider community. Therefore, education has an important role for teenagers in teaching religious knowledge which regulates the morals and manners of being a wise human being in life. As a series of words written by Einstein became a symbol that "science without religion is blind and religion without science is lame". This is focused on Madurese people who need education and guidance regarding the mindset of getting used to the carok tradition which often occurs in their area. One solution to respond to this is to present the teaching method of previous ulama in the spread of Islam, namely Islamic boarding schools. Of course, an Islamic boarding school has a strong influence with the background of an ahlul ’ilm scholar who is a role model and role model for its students. And the life presented at the Islamic boarding school will form the intended wisdom, namely revolutionizing the wrong culture on the island of Madura with the methods or regulations presented by the Islamic boarding school.